БАДИИЙ АДАБИЁТДА МУТЕЛИК ПСИХОЛОГИЯСИ (Scientific journal of the Fergana State University, 2023)
This article describes the psychology of dependence which given in literature of the Period of Independence. The fate of Uzbek women, the fortune of youth, the view of dependence to be discussed.